BOLTING OF CHINESE CABBAGE INFLUENCED BY FERTILIZATION AND CULTIVATION PLACE - Eniko Laczi; E. Luca; Adelina Dumitras; Laura Luca; Felicia Butuza Bumb; Paunita Boanca (Agricultura, 2015)
The main aim of the experiment was to study the behavior of several hybrids of Chinese cabbage cultivated in protected places and open field when different types of manures were applied. The research took place in Poieni, a small village near Cluj Napoca, in a polyethylene tunnel, respectively in open field, and involved three hybrids: Golden Wa-Wa, Vitimo and Hybrid Super. Cattle and horse manure was applied before planting and in the vegetative period. Results showed that bolting of Chinese cabbage was influenced by cultivation place - best results (1.41% of bolted plants) were registered in the case of protected crops; by fertilization - a higher number of plants bolted (3.39%) when no fertilizers were added and by planting material - a lower bolting ratio (1.31%) was registered at Hybrid Super. It can be concluded that bolting of Chinese cabbage can be reduced by choosing the right planting material combined with an improved cultivation technology.